Updating Poe: The Adaptation of 'The Pit and the Pendulum' into Comic in Nevermore (2008) - Abizanda Cardona, María (Journal of Artistic Creation and Literary Research, 2025)
The writings of Edgar Allan Poe have been adapted into comic strips in over two hundred works since 1940. Most recent versions have stepped away from traditional to-the-letter retellings of the Bostonian's celebrated stories, and have favored instead creative rewritings aimed at addressing modern-day concerns. Drawing from Linda Hutcheon's approach to adaptation as a process of original reception and creation liable to engage in a larger social critique, this essay will carry out a comparative analysis of Poe's 1842 short story "The Pit and the Pendulum" and its reworking into a comic format by James Delano and Steve Pugh, collected in Nevermore: A Graphic Adaptation of Edgar Allan Poe's Short Stories (2008). If Poe's original has been read by critics as an exposé of institutionalized torture, judicial corruption, and the disciplining role of prison in 19th-century penitentiaries, allegorized in the medieval Toledo, Delano and Pugh's version translates the tale to our days to condemn the perpetuation of these practices, aggravated by the advancement of technology and mass media. In this revision, Delano and Pugh exploit comic-specific techniques to increase readers' identification, thus harnessing the remediation of Poe's story to update and amplify Poe's critique of state-sanctioned torture.